(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Based on research and analysis of information of rare species and plant communities of Volyns’ka Upland, a list of rare communities and species that require protection at national and regional levels is given. The characteristics and representativeness of rare forest plant communities of the region with detailed study of their characteristics are specified. The list of plant communities that are rare in the region is given and the feasibility of preserving and further investigation is proved. Priority focus on today is the study of forest ecosystems as they provide conservation and restoration of biodiversity at all levels of organization of living organisms. 15 species of rare plants, included into the Red Data Book of Ukraine and 20 species from the regional Red lists were found in the forests of Volhynian upland. The list of rare plant communities counts 4 associations included into the Green Data Book of Ukraine and 3 associations that were proposed for the regional protection.